Mengapa Sociopreneur Bukan Social Entrepreneur? - M. Yusuf Azwar Anas (DIALEKTIKA: Jurnal Ekonomi dan Ilmu Sosial, 2019)
Acronyms are often used in Indonesia by many groups, or provide a new term for a particular activity. Naming an activity by providing an acronym or combining words will generate a new acronym. The emergence of a new term, even though its essence has not undergone significant changes, requires someone to understand the term more deeply, so as not to misinterpret it. This article attempts to provide an explanation regarding the many acronyms that are often used in writing which can confuse readers. There are many acronyms in the term entrepreneur which are associated with certain activities, for example entrepreneur which is associated with digital, social, and technology. The focus of this article is to discuss the ambiguity between the terms social entrepreneur or sociopreneur, so that readers get clarity in interpreting each term used. This study uses the literature review method, namely by examining various literature on the results of previous studies.